Empowering English Learning beyond Borders: Challenges and Benefits of Extracurricular Activities in a Non-Anglosphere Context - Le, Thanh Thao; Le, Xuan Mai; Nguyen, Thanh-Tung; Nguyen Thi, Kim-Thanh (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
English language assumes a pivotal position in the socioeconomic advancement of Vietnam. The adoption of extracurricular mechanisms for English language acquisition is recognized as an innovative and potent overhaul of the pedagogical framework for English learners in Vietnam. This study was executed employing a quantitative methodology to ascertain the perceptions of tertiary level students regarding the advantages and obstacles encountered in their engagement with extracurricular activities directed at English language acquisition. Data was accumulated from 1,032 students pursuing higher education in an institution situated in the Mekong delta, facilitated by a questionnaire. The findings highlighted significant expectations students harbored for these activities. Particularly, they anticipated that engagement in these extracurricular endeavors would yield a positive influence on their linguistic competencies, while also fostering a conducive and collaborative environment for English language acquisition, thereby expanding their social networks with fellow participants. Nevertheless, the participants also acknowledged potential drawbacks. They expressed concern that participation in these activities might be time-consuming and could potentially diminish their motivation to partake, especially if the activities were not in alignment with their individual competencies and areas of interest. The findings of this study propose implications for enhancing the effectiveness of extracurricular activities for English language acquisition. Specifically, adequate financial and human capital investment is crucial, and the activities need to be meticulously planned to avoid an excessive time commitment from the students.